Nanostructured carbon-doped α-Al2O3 microspheres: Scalable synthesis and luminescence properties - Pankaj Singh; Jitendra Bahadur; Shiv Govind Singh; Durgesh Singh Sisodiya; Ras Bihari Rakesh; Debasis Sen; Shashwati Sen (Next Materials)
This study presents a novel method of synthesizing alumina doped with carbon through the scalable spray drying process. In the first step nanostructured Al(OH)3 microspheres are synthesized by spray drying with excellent flowability, narrow size distribution, and controlled morphology. Sintering of Al(OH)3 microspheres at 1400°C produced the α-Al2O3 phase which is carbon doped by immersing sintered samples in acetone, followed by heat treatment at 900°C. UV-Vis spectra confirmed the formation of F and F+ centers corroborating the incorporation of oxygen vacancy in the Al2O3 lattice. The synthesized microspheres have been characterized using XRD, SAXS and other techniques. Preliminary studies are also reported on the thermoluminescence measurements which indicate that the synthesized α-Al2O3:C microspheres can be tailored for high-dose dosimetry applications, with the potential for more efficient, cost-effective, and scalable production compared to traditional synthesis methods.